The Effect of Compensation and Work Stress on the Performance of Honorary Employees with Work Discipline as a Mediation Variable in the Regional Secretariat Manokwari Regency - Widya Fira Lestari; I Made Sara; I Wayan Gde Sarmawa (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to analyze the effect of compensation and work stress on the performance of honorary employees with work discipline as a mediating variable at the Regional Secretariat of Manokwari Regency. The research employed a quantitative approach using a survey method. The population consisted of all honorary employees at the Regional Secretariat of Manokwari Regency, with sample determination using an appropriate technique and data collection conducted through a closed-ended questionnaire. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that compensation has a positive and significant effect on both work discipline and the performance of honorary employees. Work discipline also has a positive and significant effect on employee performance. In contrast, work stress does not have a significant effect on either work discipline or employee performance. Regarding the mediating role, work discipline is not proven to significantly mediate the relationship between compensation and employee performance (no mediation based on the indirect effect), nor does it mediate the relationship between work stress and employee performance. These findings emphasize that improving the performance of honorary employees is more effectively achieved by strengthening compensation systems and work discipline rather than solely managing work stress. Civil servants are an important element in the administration of government.